Composición florística y estructural para el bosque primario del hotel la Laguna del Lagarto Lodge, Boca Tapada de Pital, San Carlos, Alajuela, Costa Rica. - Quirós-Brenes, Kenner Gerardo (Instituto Tecnológico de Costa Rica, 2002)
The floristic and structural composition for the primary forest og the Hotel La Laguna of Lagarto Lodge, Boca Tapada of Pital, San Carlos, Costa Rica, was analyzed. Eight permanent sampling parcels were established (2500 m2). Moderate overall height, diameter, position and crown shape of individuals greater than 10 cm diameter, were measured. A high heterogeneity of the forest was determinated, with 140 species within the permanent sampling parcels. Others species were not detected due to method but were observed within the forest. Some are endangered and their extraction has been banned by the Executive Decree N° 25 700 of January of 1997. They are Hymenolobium mesoamericanum, Podocarpus guatemalensis, Sclerolobium costaricense and Platymiscium pinnatum. There are not dominant species in any particular site. This characteristic make the forest ideal for ecotouristics activities development, combinated to a regular topography that allows the easy journeys to the tourists through the network of existing pathways. It is important for this forest to maintains its present condition and that it can pffer to the tourist the possibility of enjoying the wealth of the rain tropical forests, preserving and protecting the ecosystem that allows the perpetuantion of the species that conform it
Proyecto de Graduación (Bachillerato en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2002.
Keywords: Especies; Diversidad florística; Trópicos; Muestreo; Factores bioticos; Energía